Mercy Watson : something wonky this way comes - DiCamillo, Kate.; Van Dusen, Chris (Somerville, MA : Candlewick Press, 2009)
Mr. and Mrs. Watson think it is a wonderful idea to bring their pet pig Mercy to the drive-in, and when Mercy arrives, she sets off on a mission to find her own buttery bucket of popcorn, much to the dismay of the other movie patrons.
Horn Book.
School Library Journal.
Horn Book, April 2010.
School Library Journal, August 2009.
2.4
K-3
Keywords: Drive-in theaters -- Juvenile fiction; Swine as pets -- Juvenile fiction; Watson, Mercy (Fictitious character) -- Juvenile fiction; Drive-in theaters -- Fiction; Pets -- Fiction; Pigs -- Fiction; Watson, Mercy (Fictitious character) -- Fiction; Drive-in theaters -- Fiction; Humorous fiction; Pets -- Fiction; Pigs -- Fiction; Watson, Mercy (Fictional character) -- Fiction; Humorous fiction